Dysfunctionality of the concept of a family household provided for in the Act on shaping the agricultural system - Leśkiewicz, Katarzyna (Przegląd Prawa Rolnego, 2023)
The premise underlying the conducted considerations is the assertion that the concept of a family household as provided for in the Act on shaping the agricultural system is dysfunctional. Firstly, the theoretical aspects of defining concepts and their functions are presented, followed by an analysis of the concept of a family holding made against the background of its formulation in the regulations in other countries. It is then concluded that the defective definition of this concept hinders the protective function of the family holding which is to secure the family character of farms, their profitability and efficiency. The analysis of the stabilising and dynamising functions of the definition of a family holding also gives rise to the claim that this definition fails to possess the characteristics that would be conducive to the strengthening of such farms and increasing their economic efficiency. A defective definition of a family holding prevents satisfactory protection of the values specified in the Constitution, and consequently obstructs the achievement of the objectives of the Act on shaping the agricultural system in Poland.